The impact of COVID-19 on epilepsy care: Perspectives from UK healthcare workers - Thorpe, J; Ashby, S; Cross, JH; Sander, JW; Newton, C; Hanna, J; Sen, A (Elsevier, 2021)
The COVID-19 pandemic has created an immense pressure on healthcare providers, resulting in a shift to remote consultations and the redeployment of healthcare workers (HCWs). We present survey data from the United Kingdom (UK) HCWs to outline how changes in healthcare provision impact clinicians' wellbeing and ability to provide adequate care. We designed an online survey to gather the experiences of HCWs providing care to people with epilepsy. We received seventy-nine responses from UK-based HCWs, of whom 43% reported an impact on their mental health. Changes to service delivery have resulted in 71% of clinicians performing > 75% of their consultations remotely. Diagnosing and treating epilepsy has changed, with a fifth of respondents being significantly less confident in diagnosing epilepsy. Ultimately, these results show that COVID-19 has had an overall negative impact on HCWs and their ability to provide epilepsy care. These results must be considered when reorganizing health services to ensure optimal outcomes for people with epilepsy.